Thermal Comfort in the Overhead Public Space in Hot and Humid Climates: A Study in Shenzhen - Xie, Xiaohuan; Liao, Haitao; Wang, Ruobing; Gou, Zhonghua (Buildings (Basel), 2022)
In recent years, semi-outdoor space has become an important research subject in the field of thermal comfort. Overhead space located on the ground floor is a common type of semi-outdoor space in China’s Lingnan region with a hot and humid climate. Its thermal comfort has been scarcely studied. This study aims to reveal the importance and influencing factors of overhead public spaces in hot and humid areas, and to explore the corresponding adaptive behaviors of people. In this research, several overhead public spaces in Shenzhen University were selected to conduct field measurements and questionnaire surveys (n = 509) in hot and cold seasons. The results indicated that the acceptable physiologically equivalent temperature (PET) range for 90% of the population was 26.2–30.4 °C in hot season, 9.9–19.2 °C in cold season, and 17.6–25.3 °C for the whole year. The respondents preferred “neutral” in cold season and “slightly cool” in hot season. Respondents in hot season were more eager to adjust their thermal comfort, while those in cold season were more comfortable exposing themselves to the sun. Concurrently, the neutral temperature and neutral temperature range for different seasons was obtained and compared with the results of other studies. The results provide references for thermal comfort adjustment in hot and humid areas as well as optimization suggestions for the planning and design of overhead spaces.